Development of Teaching-Based Modules Brain Based Learning by Using Games in Mathematics Learning at Yapis Ranting 2 Middle School Timika - hanudin, sub; Herwin, Herwin; Rasul, A. Rasul (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The aim of this research is to determine the feasibility of developing a brain-based learning mathematics module using a crossword puzzle game as seen from the level of validity, practicality and effectiveness. The method used is research and development with the ADDIE research design. This research was conducted at Yapis Ranting 2 Middle School with test subjects of 27 class VIII students. The validity results show that media validation reached a percentage of 83.33% and material validation was 89.98% in the